2021
DOI: 10.1007/s10668-021-01275-6
|View full text |Cite
|
Sign up to set email alerts
|

The nexus of tourism, renewable energy, income, and environmental quality: an empirical analysis of Pakistan

Abstract: In the current study, we investigate the dynamic association of tourism, renewable energy, income, foreign direct investment (FDI), and carbon dioxide (CO 2 e) for Pakistan over 1990-2017. We established four plausible hypotheses and verified by employing the autoregressive distributed lags model and Granger causality based on vector error correction model (VECM). Considering the cointegration relationship between the variables, the outcomes of autoregressive distributed lags suggested that tourism increases e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…This proposition is based on the EKC phenomenon, which states that increased international tourism demand increases energy demand, which leads to a rise in environmental quality (Katircioglu 2014a , b ; Stern 2004 ). Zhang and Liu (2019), cited in Bano et al ( 2021 ), showed that enhancing tourist growth in the long run can aid in the regeneration of environmental infrastructure in ten nations in Northeast and South-East Asia. Tourism is, nevertheless, regarded as a critical part of the environment in this region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This proposition is based on the EKC phenomenon, which states that increased international tourism demand increases energy demand, which leads to a rise in environmental quality (Katircioglu 2014a , b ; Stern 2004 ). Zhang and Liu (2019), cited in Bano et al ( 2021 ), showed that enhancing tourist growth in the long run can aid in the regeneration of environmental infrastructure in ten nations in Northeast and South-East Asia. Tourism is, nevertheless, regarded as a critical part of the environment in this region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a positive association between tourism and renewable energy variables, as empirically pronounced by Bano and Alam (2021) also. They posit that the use of renewable energy helps in augmenting tourism, speeding up economic growth, and repelling CO 2 emissions.…”
Section: Pmg Regression and Dcce Modelmentioning
confidence: 69%
“…Belt Road countries were investigated by [110,111], SAARC and ASEAN countries [112], as well as, South Korea [113], Bangladesh [114], Malaysia [115][116][117][118], Indonesia [119][120][121][122][123], Vietnam [124], Taiwan [125], Pakistan [126][127][128][129][130], Kazakhstan [131,132], and Thailand [133]. Not many studies dealing with the African continent [134] investigate the continent, [135] sub-Saharan Africa, [136] Rwanda, [137] Cameron, Nigeria [138], [139] Ethiopia and [140] Tunisia.…”
Section: Discussionmentioning
confidence: 99%